PR communications tools in brand image and awareness building - Vertehel, Viktoriia; Вертегел, Вікторія Леонідівна (Запоріжжя: ТДАТУ, 2026)
Brand management is an effective management system for protecting intellectual property through the creation and maintenance of a company’s brand using a set of interrelated marketing elements aimed at creating long-term competitive advantages [1, 48]. PR communication tools in brand management are essential for building reputation, credibility and market presence. They are tools that brands use to reach their target audience and promote their product or service, often earned through media pitches and press releases.
Keywords: PR communications; brand image